Comparison of budesonide and beclomethasone dipropionate for treatment of asthma. Issue 8 (August 1987) - Springer, C; Avital, A; Maayan, C; Rosler, A; Godfrey, S
Abstract : Beclomethasone dipropionate (BDP) and budesonide (BUD) were each given in a dose of 200 micrograms twice daily by metered dose inhaler to 10 asthmatic children already dependent on treatment with steroids. In a double blind randomised crossover study each course lasted one month. No clinically important differences were found between the two treatments when symptom scores, symptom free days, additional use of salbutamol, and results of lung function tests were considered. Metyrapone mildly reduced the plasma concentration of 11-deoxycortisol in two patients during treatment with budesonide, and in four during treatment with beclomethasone. It is concluded that although they are usually safe, both drugs may cause mild adrenal suppression when given in a dose of 200 micrograms twice daily.